2008
DOI: 10.1021/la801735c
|View full text |Cite
|
Sign up to set email alerts
|

Defect Induced Asymmetric Pit Formation on Hydroxyapatite

Abstract: Defect sites on bone minerals play a critical role in bone remodeling processes. We investigated single crystal hydroxyapatite (100) surfaces bearing crystal defects under acidic dissolution conditions using real-time in situ atomic force microscopy. At defect sites, surface structure-dependent asymmetric hexagonal etch pits were formed, which dominated the overall dissolution rate. Meanwhile, dissolution from the flat terraces proceeded by stochastic formation of flat bottom etch pits. The resulting pit shape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
38
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 32 publications
4
38
0
2
Order By: Relevance
“…For an HAP (100) surface exposed to deionized water, the average height of each step was 0.84 ± 0.1 nm, which is close to the interlayer distance of the (100) , respectively, suggesting that steps with (110) facets were energetically less stable than steps with (010) facets, and that the (110) face could be more susceptible to dissolution [50]. Molecular steps parallel to the elongated axes of HAP crystals, and those angled at approximately 54° to the elongated axis, are not only energetically favorable but also kinetically dominant under dissolution conditions.…”
Section: Crystallization and Dissolution Modulation Of Calcium Orthopmentioning
confidence: 71%
“…For an HAP (100) surface exposed to deionized water, the average height of each step was 0.84 ± 0.1 nm, which is close to the interlayer distance of the (100) , respectively, suggesting that steps with (110) facets were energetically less stable than steps with (010) facets, and that the (110) face could be more susceptible to dissolution [50]. Molecular steps parallel to the elongated axes of HAP crystals, and those angled at approximately 54° to the elongated axis, are not only energetically favorable but also kinetically dominant under dissolution conditions.…”
Section: Crystallization and Dissolution Modulation Of Calcium Orthopmentioning
confidence: 71%
“…However, previously, we showed that pits with hexagonal shape formed on the (100) surface when dissolution experiments were performed in the same acidic buffer in the absence of NaCl. 7 In addition, hexagonal pit shapes were observed previously in both synthetic and biological apatites in various acidic solution environments without NaCl.…”
mentioning
confidence: 71%
“…Previously, to address this challenging problem, we investigated HAP dissolution processes by directly observing atomically well defined (100) HAP surfaces under acidic dissolution conditions using in situ atomic force microscopy (AFM). 7 We found that dissolution originating from small local structural defects (e.g., screw and edge dislocations) embedded on atomically flat terraces came to dominate the overall dissolution process by formation of hexagonal deep etch pits. Here, using the same technique, we report the effects of NaCl concentration on the HAP dissolution process.…”
mentioning
confidence: 83%
See 1 more Smart Citation
“…4 Because of its biocompatibility, HAP has been used as the model compounds for the study of biominerals. [5][6][7] One important chemical characteristic of HAP is its high ion exchange capability. It is well known that various anions such as carbonate, fluoride and chloride ions can be incorporated onto HAP surface via anion exchange with hydroxyl group in aqueous solution.…”
Section: -3mentioning
confidence: 99%